2010
DOI: 10.1017/s0022149x10000386
|View full text |Cite
|
Sign up to set email alerts
|

Polystoma okomuensisn. sp. (Monogenea: Polystomatidae) from Boulenger's striped frog,Phlyctimantis boulengeri(Perret, 1986) in Nigeria

Abstract: Polystoma okomuensis is described as a new species of the Polystomatidae parasitic in the urinary bladder of Boulenger's striped frog Phlyctimantis boulengeri in the Okomu National Park, Edo State, Nigeria. Although other African polystomes have been reported from Nigeria, this is the first to be described from the country and the first from Phlyctimantis. It is distinguished from other African Polystoma species by a combination of characters, including the body size, size and shape of the hamuli, size and sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
(30 reference statements)
1
7
1
Order By: Relevance
“…Seven toads from genus Sclerophrys and thirtyone frogs belonging to 4 genera, Hemisus, Ptychadena, Rana and Xenopus were examined out of the several seen for conservation reasons. The prevalence of infection in the observed species when compared to earlier reports in tropical Nigeria [20,23], showed that the frogs in this study had low worm burden. Previous studies from Nigeria also recorded the presence of cestodes and trematodes but only nematodes were encountered in this study.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…Seven toads from genus Sclerophrys and thirtyone frogs belonging to 4 genera, Hemisus, Ptychadena, Rana and Xenopus were examined out of the several seen for conservation reasons. The prevalence of infection in the observed species when compared to earlier reports in tropical Nigeria [20,23], showed that the frogs in this study had low worm burden. Previous studies from Nigeria also recorded the presence of cestodes and trematodes but only nematodes were encountered in this study.…”
Section: Discussionsupporting
confidence: 55%
“…Paracosmocerca mucronata was gotten from the intestine of the only Sclerophrys pentoni encountered in the study, it was reported as a parasite of Xenopus muelleri [20], this is the second time this parasite will be reported in another part of the Country. Chenospirura asturi was recovered from Sclerophrys maculata in Iwoye farm, it was reported as a parasite of water Birds [36].…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Investigations of the parasites of amphibians in Nigeria have mostly been undertaken in the forest and savannah biotopes of the country (Thurston, 1967(Thurston, , 1970Avery, 1971;Aisien and Du Preez, 2009;Aisien et al, 2001Aisien et al, , 2003Aisien et al, , 2004aAisien et al, , 2011Aisien et al, , 2015Aisien, 2012, 2015;Imasuen et al, 2012a). Investigations have also been carried out on pipid anurans (Hymenochirus curtipes and Xenopus tropicalis) obtained from the Lagos (coastal) area of the country Tinsley, 1995, 1998a, b).…”
Section: Introductionmentioning
confidence: 99%